Menyoal Kritik Orientalis terhadap Qirā’at: Studi Kritis terhadap Pemikiran Arthur Jefrey Mengenai Ragam Bacaan Al-Qur’an - Akhmad Roja Badrus Zaman (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2020)
Arthur Jeffery (1892-1959) was an Australian orientalist who was quite influential in the 20th century. He is well known for his philosophical thoughts on the Qur’an. He even wanted to restore the al-Qur’an text based on Ibn Abī Dāwud al-Sijistānī’s Kitab al-Maṣāḥif which is thought to have recorded readings (qirā’at) in several counter-manuscripts - rival codices. This article examines his thoughts on the variety of reading (qirā’at) of the al-Qur’an. The method used is descriptive-qualitative. From the study conducted, it was found that the following results were: 1) Arthur Jeffery considered that the Mushaf ‘Uthmānī which had a dot and a diacritical mark was a factor in the birth of the variety of reading for the al-Qur’an. According to him, this is a free opportunity for readers to mark themselves according to the context of the verse they understand, 2) Arthur's thought is natural because he uses a text-critical study approach to the Qur’an - as a method. it was used by the Orientalists of the Bible. 3) the use of text-critical studies of the Qur’an as done by Arthur is a fatal basic mistake, because after all the process of transmitting the Koran in the early Islamic century was an oral tradition, so the accusations made by Arthur about qirā’at It is easy to argue with, 4) The use of the term variant reading - by orientalists including Arthur Jeffery is considered a failure by Islamic thinkers in representing the meaning of qirā’at, because it implies uncertainty about the truth of the qiraat itself. So that al-A’ẓamī prefers the term multiple reading, because it is more in accordance with the historical facts of the al-Qur’an transmission which accommodates many dialects of Arabic society.